2010
DOI: 10.1111/j.1755-053x.2009.01068.x
|View full text |Cite
|
Sign up to set email alerts
|

Do Corporate Venture Capitalists Add Value to Start‐Up Firms? Evidence from IPOs and Acquisitions of VC‐Backed Companies

Abstract: "We present evidence that corporate venture capitalists (CVCs) add value to start-up companies only when the start-ups have a strategic fit with the parent corporations of CVCs. We find that CVCs provide a variety of services and support that suit the specific needs of start-ups operating in different industries. CVC-backed start-ups are able to obtain higher valuations at the IPO than non-CVC-backed ones, and the value added by CVCs concentrates in start-ups with a strategic overlap with CVC parents. Entrepre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
91
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(102 citation statements)
references
References 56 publications
(71 reference statements)
10
91
1
Order By: Relevance
“…Moreover, Alvarez-Garrido and Dushnitsky (2015), Chemmanur et al (2014) and Park and Steensma (2013) showed that after CVC involvement, ventures' innovativeness rates measured in terms of numbers of patents were higher than those of their counterparts backed by IVCs. In this regard, Ivanov and Xie (2010) found that CVCs only add value to startups that have a strategic fit with their parent organizations. Interestingly, from a CVC intra-group perspective, Gompers and Lerner (2000) reported that startup investments with a strategic fit with CVCs' parent firms, on average received a lower valuation than startup investments lacking such a relationship.…”
Section: Theoretical Development and Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, Alvarez-Garrido and Dushnitsky (2015), Chemmanur et al (2014) and Park and Steensma (2013) showed that after CVC involvement, ventures' innovativeness rates measured in terms of numbers of patents were higher than those of their counterparts backed by IVCs. In this regard, Ivanov and Xie (2010) found that CVCs only add value to startups that have a strategic fit with their parent organizations. Interestingly, from a CVC intra-group perspective, Gompers and Lerner (2000) reported that startup investments with a strategic fit with CVCs' parent firms, on average received a lower valuation than startup investments lacking such a relationship.…”
Section: Theoretical Development and Hypothesesmentioning
confidence: 99%
“…The literature distinguishes between the absorptive capacity entailed by the use of CVC as well as CVCs' value-added services supplied to startups (e.g., Dushnitsky and Lenox 2005a, b;Ivanov and Xie 2010;Maula et al 2005;Zu Knyphausen-Aufseß 2005). Absorptive capacity means that CVCs' parent organizations exploit knowledge through their venture investments, primarily to gain a window on innovative technology but also to explore new products and industry trends (Keil 2000;Maula 2007;Winters and Murfin 1988).…”
Section: Theoretical Development and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to the CVC literature dealing with a company's investment focus and its impact on corporate venturing performance, the notion of strategic fit with the parent corporation (Gompers & Lerner, 2000;Ivanov & Xie, 2010) and the concepts of the degree of relatedness (Da Gbadji, Gailly, & Schwienbacher, 2015;Yang, Narayanan, & De Carolis, 2014) and complementarities (Dushnitsky & Shaver, 2009;Park & Steensma, 2012) have been analyzed.…”
Section: Locus Of Investment: Exploration or Exploitationmentioning
confidence: 99%